MATERNAL MORTALITY AND MATERNAL «NEAR MISS»: ARE THE CURRENT BLEEDING PREVENTION ALGORITHMS WORKING? - M. S. Zainulina; D. R. Eremeeva; M. I. Krivonos (Акушерство, гинекология и репродукция, 2018)
Bleeding during pregnancy, labor and delivery is considered the major cause of maternal death or subsequent disability, and various disorders. Currently, obstetricians and gynecologists have a number of effective tools for the prevention and treatment of obstetrical bleedings. Compliance with the Federal clinical protocols (recommendations) and the development of local algorithms for the treatment and prevention of obstetric hemorrhages are consistent with the organ-preserving treatment strategy and will help reduce maternal mortality and morbidity.